Policy of Taxation of Premium Value Addition Tax (Ppnbm) on Motorwages for the Purpose of Tax Collection in Indonesia - Yofian Roesjdiansyah, Muhammad; Widya Nugraha, Raka; Febreight Arthania, Yolva (Sekolah Tinggi Ilmu Hukum Adhyaksa, 2024)
The Sales Tax on Luxury Goods (PPnBM) policy in Indonesia is designed to regulate the consumption of luxury goods, increase state revenue, and encourage the growth of local industries. This study analyzes the mechanisms of PPnBM imposition on motor vehicles and other luxury goods. The results show that the imposition of PPnBM on non-motor vehicle luxury goods is considered suboptimal. Many high-value luxury goods, such as watches, bags, and jewelry, are not the object of PPnBM, potentially weakening the principle of tax justice and reducing the country’s revenue potential. In contrast, the PPnBM policy on motor vehicles is considered effective in achieving tax collection objectives, with detailed and clear regulations categorizing tariffs based on passenger capacity, engine size, fuel consumption, and CO2 emissions levels. This study recommends expanding the scope of PPnBM to include more luxury goods and adjusting regulations to ensure fairness in tax distribution and increase state revenue.